Productive performance of cowpea-radish intercropping under different amounts of rooster tree biomass incorporated into the soil - Maria F. S. Pereira; Francisco Bezerra Neto; Frederico S. T. Pontes; Paulo C. F. Linhares; Maiele L. da Silva; Ítalo N. Silva (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Intercropping systems of cowpea with radish are beginning to be deployed in the semiarid region of Rio Grande do Norte state. The great challenge is to know whether or not there is productive efficiency in these systems when fertilized with organic matter produced by spontaneous species from the ‘Caatinga’ biome. Thus, the aim of this study was to evaluate the productive performance of cowpea-radish intercropping systems under different amounts of rooster tree biomass incorporated into the soil. The study was conducted at the experimental farm Rafael Fernandes, rural zone of Mossoró, RN, in the period from June to September 2013, in an experimental design of randomized blocks with four treatments and five replicates. The treatments consisted of the following amounts of rooster tree biomass incorporated into the soil (10, 25, 40 and 55 t ha-1 on a dry weight basis). The best productive performance of the cowpea-radish intercrop was obtained when the rooster tree biomass amount of 50.01 t ha-1 was incorporated to the soil. The use of rooster tree biomass as green manure is agronomically viable in intercropped systems of cowpea-radish.